Unlocking the Nutritional Treasure: Typhonodorum lindleyanum Schott. (Viha) after Antinutrient Removal - Letsara Rokiman; Rajaovelo Andry Tsimioly; Razafindrahaja Vololotahina; Ratalata Baovola; Fatiany Pierre Ruphin; Ralaivaon-Tsitonta Jumael Edith Fabrice; Ngbolua Koto-Te-Nyiwa Jean Paul; Robijaona Rahelivololona Baholy (Britain International of Exact Sciences (BIoEx) Journal, 2025)
Viha (Typhonodorum lindleyanum) presents a promising avenue for enhancing food security and addressing malnutrition in Madagascar, particularly in the face of climate change. This study comprehensively characterized the nutritional and phytochemical properties of Viha, considering the impact of processing methods on its edibility and potential health benefits. Our findings reveal a diverse nutritional profile across Viha plant parts. Rhizomes, rich in carbohydrates, exhibited significant variations in micronutrient content depending on cooking methods. Steaming enhanced iron and potassium, while boiling reduced calcium and phosphorus. Viha seeds demonstrated a relatively stable micronutrient profile across preparations, while leaves were rich in potassium, phosphorus, and iron. Furthermore, the study identified a rich array of phytochemicals, including tannins, flavonoids, and leucoanthocyanidins. While the presence of antinutrients such as phytate and oxalate requires careful consideration, appropriate processing methods can mitigate their impact. These findings suggest that Viha, with proper processing and utilization, could serve as a valuable food source, enhancing dietary diversity and nutritional security, especially in regions vulnerable to climate change impacts such as droughts and food shortages. Further research is warranted to optimize processing methods, enhance nutrient bioavailability, and explore sustainable cultivation and utilization strategies for Viha as a climate-resilient food source in Madagascar.